Peroral Endoscopic Myotomy for Achalasia after Bariatric Surgery: A Case Report and Review of the Literature - Maselli, Roberta; Fiacca, Matteo; Pellegatta, Gaia; de Sire, Roberto; De Blasio, Federico; Capogreco, Antonio; Galtieri, Piera; Massimi, Davide; Trotta, Manuela; Hassan, Cesare; Repici, Alessandro (Diagnostics (Basel), 2023)
Introduction: Achalasia following bariatric surgery is a rare phenomenon with diverse potential physiopathological origins. Aims: This article aims to explore the hypothetical physiopathological connection between bariatric surgery and the subsequent onset of achalasia. Material and Methods: A review was conducted to identify studies reporting cases of peroral endoscopic myotomy (POEM) after bariatric procedures and detailing the outcomes in terms of the technical and clinical success. Additionally, a case of a successful POEM performed on a patient two years after undergoing laparoscopic sleeve gastrectomy (LSG) is presented. Results: The selection criteria yielded eight studies encompassing 40 patients treated with POEM for achalasia after bariatric surgery: 34 after Roux-en-Y gastric bypass (RYGB) and 6 after LSG. The studies reported an overall technical success rate of 97.5%, with clinical success achieved in 85% of cases. Adverse events were minimal, with only one case of esophageal leak treated endoscopically. However, a postprocedural symptomatic evaluation was notably lacking in most of the included studies. Conclusions: Achalasia poses a considerable challenge within the bariatric surgery population. POEM has emerged as a technically viable and safe intervention for this patient demographic, providing an effective treatment option where surgical alternatives for achalasia are limited. Our findings highlight the promising outcomes of POEM in these patients, but the existing data remain limited. Hence, prospective studies are needed to elucidate the optimal pre-surgical assessment and timing of endoscopic procedures for optimizing outcomes.